Human Resource Management of Vegetable and Fruit Chips Agroindustry at PT. Inovasi Pangan Lestari - Tjokorda Istri Mas Smaradewi; Anak Agung Ayu Wulandira Sawitri Djelantik; I Made Sudarma; Ary Bakhtiar (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2025)
Human resources play a crucial role in a company's success, including PT Inovasi Pangan Lestari, an MSME-scale agro-industrial company in Malang. Despite its commitment to improving agricultural output and product distribution, the company's human resource management still needs attention. Informal performance appraisals, unstructured organization, and lack of an optimal supervisory system are the main challenges. This study aims to determine the application of human resource management functions at PT Inovasi Pangan Lestari, including planning, organizing, directing, and controlling, and relate it to theory and previous studies so that it can be an evaluation for PT Inovasi Pangan Lestari and other agro-industrial companies to improve productivity and company performance. The research method used is descriptive qualitative. The data analysis method used is thematic analysis through open coding, axial coding, and selective coding. The results obtained are that human resource management practices are still simple and managed directly by the board of directors. PT Inovasi Pangan Lestari faces challenges in managing human resources because the company is still in the growth stage. For this reason, the company needs to set up a structured organization, improve employee briefings, and ensure objective and transparent performance evaluations to identify appropriate training needs.